2005
DOI: 10.1007/s00268-005-7670-y
|View full text |Cite
|
Sign up to set email alerts
|

Adult Surgical Emergencies in a Developing Country: The Experience of Nnamdi Azikiwe University Teaching Hospital, Nnewi, Anambra State, Nigeria

Abstract: The goal of this study was to examine the adult surgical emergencies seen at the Nnamdi Azikiwe University Teaching Hospital (NAUTH), Nnewi, with a view to proffering preventive solutions where appropriate and improving outcome. From the register of patients seen at the Casualty department and from the operations register in the main operation room of NAUTH, names and hospital numbers of adult patients treated as emergencies over a 5-year period, from 7 September 1998 to 6 September 2003, were obtained. The ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
17
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 15 publications
6
17
1
1
Order By: Relevance
“…[13] This obviously indicates that complication rate of acute appendicitis is increasing in children in our environment, mainly due to ignorance on the part of parents about the disease, self-medication and delay in reporting to hospital. According to reports from the same hospital [14] and also from Nigeria, [15] in adults the most common abdominal emergency was acute appendicitis, accounting for over 22% and 15%, respectively, of all acute surgical admissions for abdominal pain; this was followed by typhoid ileal perforation [14] -a reversal of the situation seen in children in this study. This may be due to the fact that acute appendicitis is less common in young children, especially children under the age of 5 years.…”
Section: Discussionsupporting
confidence: 46%
“…[13] This obviously indicates that complication rate of acute appendicitis is increasing in children in our environment, mainly due to ignorance on the part of parents about the disease, self-medication and delay in reporting to hospital. According to reports from the same hospital [14] and also from Nigeria, [15] in adults the most common abdominal emergency was acute appendicitis, accounting for over 22% and 15%, respectively, of all acute surgical admissions for abdominal pain; this was followed by typhoid ileal perforation [14] -a reversal of the situation seen in children in this study. This may be due to the fact that acute appendicitis is less common in young children, especially children under the age of 5 years.…”
Section: Discussionsupporting
confidence: 46%
“…In all these and similar reports, abdominal injury with splenic damage was very common both in children as well as in adults [10,11]. In the report of Chinakwana et al [12] in Eastern part of Nigeria, RTA accounted for the second most common emergency operation after acute appendicitis. Smith et al in Liverpool [13] and Sayes et al in Birmingham [14], both in the United Kingdom reported RTA as the main cause of abdominal trauma in their studies.…”
Section: Discussionmentioning
confidence: 86%
“…[5][6][7][8][9][10] This is the first survey to assess the status of essential and emergency surgical care and of anaesthesia services in the Gambia. The most striking finding was the absence of any facilities equipped with all of the physical resources needed to provide emergency and essential surgical care.…”
Section: Discussionmentioning
confidence: 99%